Algeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix examines the possible policy responses of Algeria to the reduction of fiscal revenue and the deterioration of the external balance, and more generally the negative wealth effect on the country, stemming from the decline in oil prices. The paper highlights that in policymaking, a distinction between permanent and temporary shocks is necessarily blurred and does not contribute to working out pragmatic solutions. The paper also examines the privatization process in Algeria.